Strategi Pengembangan SDM dalam Meningkatkan Kinerja Karyawan Baitul Mal Forum Komunikasi Aktivis Masjid Kota Surakarta - Mumin Riyanto; Arif Effendi; Agus Fatuh Widoyo; Muhammad Fatchurrohman (Pawarta: Journal of Communication and Da'wah, 2023)
This research wish to know the strategy for developing human resources at the Baitul Mal Forum Komunikasi Aktivis Masjid (FKAM); wish to know the implications of human resource development strategies on improving employee performance Baitul Mal FKAM. This research used qualitative descriptive to reveal facts, phenomena, and circumstances that occurred during the research and present it as it is. Subject in this study are employees at Baitul Mal FKAM in Surakarta 2022. Primary data sources are obtained from the Director, Head of HRD, Head of Program Division, Head of Fundraising Division, Head of Finance Division and Head of Marketing Communications Division. Meanwhile, secondary data sources were obtained through literature study, namely books, documents and archives that are relevant to the research topic. The results showed that HRD's strategy carried out by Baitul Mal FKAM includes several forms, That are recruitment, training that classified into internal and external training, and the strengthening motivation work. The performance of Baitul Mal employees is quite good, but there are still obstacles, so that the knowledge after participating in the training has not been fully applied to the maximum.